Body Image Satisfaction, Social Media Usage, Self Esteem as Determinants of Selfie Obsession and Psychological Well Being - Kaur, Manpreet (My University, 2019)
The aim of the study was to examine the effect of Body Image Satisfaction and Social Media Usage on Psychological Well Being, Selfie Obsession and Self Esteem, also to investigate the impact of self esteem on psychological well being and selfie obsession and to find the gender difference among all the variables. The total sample for the study comprised of 100 participants i.e 50 male and 50 female young adults, with age range of 18-25 years. Self administered questionnaires was used to collect the data, comprising of Mutli dimensional self body relations questionnaire, Social media addiction scale, Ryffs‟ psychological well being scale, Selfitis addiction scale ,Rosenberg self esteem scale. For result analysis descriptive statistics, regression and correlation were used. Findings revealed that there exists no gender difference in body image satisfaction, social media usage, psychological well being, selfie obsession and self esteem. The results also revealed that there exists a significant positive relationship between body image satisfaction, psychological well being and self esteem it implies that the higher the satisfaction with the body image the higher will be their well being and self esteem. A negative correlation exists between social media usage and psychological well being, and a positive correlation with selfie obsession, Study revealed that social media usage has no relation with a person‟s self esteem. Another outcome of the study revealed that the better the mental well being of an individual the higher will be their self esteem.
Keywords: Selfie obsession; Social media usage; Body image; Self-esteem; Psychological wellbeing